Removal of toxic aliphatic amines by adsorption using commercial activated charcoal - Iqbal, Y.; Ahmad , N.; Ihsanullah,; Saleem, M. (Universiti Kebangsaan Malaysia, 2005)
The present study was to investigate the use of granular activated charcoal (GAC) as a potential material for removal of toxic aliphatic compounds by adsorption. Commercial granular charcoal was degassed at 105°C, 300°C and 800°C for a period of twenty-four hours, which was then used as an adsorbent for the adsorption of methylamine, dimethylamine and trimethylamine from their aqueous solutions at 25°C. The time dependence studies showed that four hours are the optimum time for the maximum adsorption of the alkylamines, irrespective of their nature and concentrations (0.005M & 0.01M). Adsorption was greater from higher concentration than lower concentration of adsorbate solution. Lower adsorption of alkylamines was observed when the charcoal was evacuated at high temperature. The adsorption sequence of alkylamines followed the order dimethylamine > trimethylamine > methylamine. The amount of adsorption using different adsorption isotherm, i.e. Freundlich and Langmuir were evaluated. L-type isotherms were also observed for the adsorption data. Further, the Langmuir and Freundlich isotherms were found applicable to the adsorption data and the values of the adsorption capacity i.e. "k" and monolayer adsorption capacity "b" were calculated and in agreement with the adsorption pattern